Transitioning to Sustainable Healthcare: Decarbonising Healthcare Clinics, a Literature Review - David Duindam (Challenges, 2022)
Background: Climate change is one of the largest threats to human health and well-being globally. The healthcare industry itself currently contributes to fueling the climate crisis with its emissions and material consumption. There has been much research on decarbonising hospitals ecological/carbon footprints but very limited study on ways to assist healthcare clinics in transitioning to a low-carbon healthcare system. Methods: A structured literature review was conducted, and the results analysed. Results: The literature review revealed four important areas to act upon to decarbonise a healthcare clinic most efficiently. These are: energy use, waste minimisation/management, the behaviors/attitudes of staff, and decarbonising the supply chain. Conclusions: The pooled literature reveals an evidence-based set of recommendations or guiding principles to decarbonise healthcare clinics the most effectively. To maximise operational effectiveness, how this is achieved will differ between clinics. Although this research is written with reference to Australia, these identified ini-tiatives are likely to be relatable to many other countries healthcare systems. Decarbonising health clinics will contribute to a sector-wide transition to more sustainable healthcare that will lead to improved environmental, social, economic and health outcomes.